2020
DOI: 10.1038/s41467-020-17829-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of erythrocyte signalling pathways during Plasmodium falciparum infection identifies targets for host-directed antimalarial intervention

Abstract: Intracellular pathogens mobilize host signaling pathways of their host cell to promote their own survival. Evidence is emerging that signal transduction elements are activated in anucleated erythrocytes in response to infection with malaria parasites, but the extent of this phenomenon remains unknown. Here, we fill this knowledge gap through a comprehensive and dynamic assessment of host erythrocyte signaling during infection with Plasmodium falciparum. We used arrays of 878 antibodies directed against human s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 74 publications
2
64
0
Order By: Relevance
“…Recently, Adderley et al . (2020) demonstrated the feasibility of targeting the host’s erythrocyte signaling pathways as an antiplasmodial strategy [ 52 ]. While this specific mechanism does not seem to be present in the DLAe material, a variety of possible mechanisms have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Adderley et al . (2020) demonstrated the feasibility of targeting the host’s erythrocyte signaling pathways as an antiplasmodial strategy [ 52 ]. While this specific mechanism does not seem to be present in the DLAe material, a variety of possible mechanisms have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between in-vitro and in-vivo activities of the plant material suggests that there is an important interaction between the host and the DLA that potentiates therapeutic activity. Recently, Adderley et al (2020) demonstrated the feasibility of targeting the host's erythrocyte signaling pathways as an antiplasmodial strategy [52]. While this specific mechanism does not seem to be present in the DLAe material, a variety of possible mechanisms have been proposed.…”
Section: Plos Onementioning
confidence: 99%
“…falciparum life cycle, and that its inhibition terminates the life cycle by preventing merozoite egress from the infected RBC. Data supporting this contention include the observations that i) band 3 tyrosine phosphorylation dramatically increases as parasite maturation progresses [ 23 , 24 , 37 ], ii) Syk is the major erythrocyte tyrosine kinase found to phosphorylate band 3 in vivo [ 21 , 51 ], iii) Syk is progressively activated and recruited to the RBC membrane as the parasite matures [ 23 , 52 , 53 ], iv) all known Syk inhibitors (and band 3 tyrosine phosphorylation inhibitors) display antimalarial activity [ 24 , 37 ], and v) incubation of parasite cultures with Syk inhibitors does not significantly alter earlier stages of parasite maturation even though the rise in band 3 tyrosine phosphorylation begins early and increases as the parasite progresses through its life cycle [ 24 , 37 ]. Collectively, these results argue that Syk kinase inhibitors interrupt a critical step required for parasite escape from its RBC host.…”
Section: Discussionmentioning
confidence: 99%
“…This positions the antibody microarray as an ideal system to assess the signalling environment inside human cells in disease and infection settings. We have applied microarrays in our efforts to understand how intracellular pathogens alter their host cells during development and identified a number of key host proteins essential to the proliferation of various pathogens 10-12 . However, the datasets obtained from antibody microarray experiments are quite complex and ultimately difficult to interpret holistically.…”
Section: Introductionmentioning
confidence: 99%
“…The network analysis strategy designed here was formulated using PhosphoAtlas 8 as a framework, which was adapted to includes the effect of the phosphorylation interactions and curated to include connections provided by the microarray developer (Kinexus). To develop a random walks-based function, we used the published datasets on the blood-stage develop of the human malaria parasite, Plasmodium falciparum 10 . This consisted of; a control dataset (uninfected red blood cells) and three parasite-infected datasets which coincide with the major distinguishable stages of parasite development (see published work for more detail 10 ).…”
Section: Introductionmentioning
confidence: 99%